THE ANALYSIS OF SYNONYMS ON WANCI DIALECT IN KEPULAUAN TUKANG BESI LANGUAGE (A Case Study at Liya Togo Village) - Sunarti, Sunarti; Tambunan, Tambunan; Miliha, La (Universitas Halu Oleo, 2020)
This study aimed at investigating the synonym on Wanci Dialect (WD) in Kepulauan Tukang Besi Language (KTBL) at Liya Togo village. The research questions of this study were “What are the forms of synonym and how are the synonyms of KTBL used? ‟. Relating to the research question above, the researcher formulates two main objectives namely: to describe clearly the synonym found in WD and the use of every synonym in WD. The researcher used a qualitative approach with a case study design. The data found out from the informants. The utility of this research is as additional information about synonym found in WD to increase and maintain the local language. This research only focuses on noun, verb and adjective categories. The Result of this research shows that in Kepulauan Tukang Besi where Wanci dialect spoken especially at Liya Togo Village, there were nine nouns that are synonymous. Then, there were three adjectives that are synonymous. In addition, there were fifteen verbs that are synonymous.